Associations between insulin resistance and low back pain risk in US adults: a cross-sectional study - Que, Zhiqiang; Chen, Dingqiang; Cai, Huirong; Lan, Weibin; Huang, Yuxuan; Rui, Gang (Frontiers in Medicine, 2025)
BackgroundInsulin resistance is one of the major pathophysiological features of type 2 diabetes mellitus. Studies have revealed the association between type 2 diabetes mellitus and low back pain. However, few studies explored the relationship between insulin resistance and low back pain directly. Therefore, this study selected HOMA-IR, TyG, TyG-BMI, TyG-WC, and TyG-WtHR as indicators of insulin resistance to comprehensively investigate the association between insulin resistance and low back pain.MethodsThe data for this cross-sectional study were from NHANES. Multivariate logistic regression was used to assess the association of insulin resistance with low back pain, and the stability of the results was evaluated by stratified analysis.ResultsA total of 6,126 adult participants were included in the study, including 3,657 non-LBP participants and 2,469 LBP patients. All of these five indices showed significant association with low back pain after full adjustment for all covariates (Model 3), HOMA-IR [OR = 1.052, 95% CI (1.018, 1.087), p = 0.003], TyG [OR = 1.431, 95% CI (1.013, 2.021), p = 0.042], TyG-BMI [OR = 1.003, 95% CI (1.002, 1.005), p < 0.0001], TyG-WC [OR = 1.001, 95% CI (1.001, 1.002), p < 0.0001], TyG-WtHR [OR = 1.268, 95% CI (1.155, 1.393), p < 0.0001]. The relationship between insulin resistance and low back pain is stable in most stratified populations (p-interaction >0.05).ConclusionInsulin resistance is associated with an increased risk of low back pain. The HOMA-IR, TyG, TyG-WC, TyG-BMI, and TyG-WtHR all showed a stable correlation with low back pain. TyG-BMI, TyG-WC, and TyG-WtHR are more stable in their associations with low back pain than TyG alone.